Effects of green coffee aqueous extract supplementation on glycemic indices, lipid profile, CRP, and malondialdehyde in patients with type 2 diabetes: a randomized, double-blind, placebo-controlled trial - Khalili-Moghadam, Sajad; Hedayati, Mehdi; Golzarand, Mahdieh; Mirmiran, Parvin (Frontiers in Nutrition, 2023)
Background/objectives: Studies have reported the health benefits of green coffee extract (GCE) in experimental models. In the current study, we aimed to determine whether supplementation with GCE improves glycemic indices, inflammation, and oxidative stress in patients with type 2 diabetes (T2D). Methods and Study Design: This randomized, double-blind, placebo-controlled trial included 44 patients (26 male and 18 female) with T2D and overweight/obesity. After blocked randomization, patients received either capsules containing 400 mg GCE twice per day (n = 22) or a placebo (n = 22) and were followed for 10 weeks. In this study, glycemic indices, lipid profiles, anthropometric examinations, blood pressure, high-sensitivity C-reactive protein (hs-CRP), and malondialdehyde (MDA) were measured twice; at baseline and at the end of the study. Results: After 10 weeks of supplementation, GCE supplementation significantly reduced body weight (P = 0.04) and body mass index (BMI) (P = 0.03) compared to the placebo. The ITT analysis indicated patients in the GCE group had a lower fasting blood glucose (FBG) concentration compared to the placebo group; however, this decreasing was marginally significant (8.48 ± 8.41 vs. 1.70 ± 5.82 mg/dL, P = 0.05) than the placebo group. There was no significant difference in insulin levels and HOMA-IR between the groups. At the end of the study, significant changes in systolic blood pressure (SBP) (P = 0.01), triglyceride (TG) level (P = 0.02), high-density lipoprotein (HDL) (P = 0.001), and TG-to-HDL ratio (P = 0.001) were found between the intervention and placebo groups. Our trial indicated GCE supplementation had no effect on diastolic blood pressure (DBP), low-density lipoprotein (LDL), or total cholesterol. During the supplementation period, the hs-CRP level significantly decreased in the GCE group compared to the placebo group (P = 0.02). No significant changes were observed in the MDA level between the two groups at the end of the study (P = 0.54). Conclusions: Our findings showed beneficial effects of GCE on SBP, TG, hs-CRP, and HDL levels in patients with T2D over a 10-week period of supplementation. Clinical trial register: [https://en.irct.ir/trial/48549], identifier [IRCT20090203001640N18].